Cough Syncope due to ACE Inhibitor - Filiz Koc; Mehmet Taylan Pekoz; Hacer Bozdemir (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Syncope is defined as a transient loss of consciousness due to sudden temporary decline in cerebral perfusion. Cough syncope is classically seen in middle aged obese men with obstructive pulmonary disease. In patients that use Angiotensin converting enzyme (ACE) inhibitors, a dry persistent cough can emerge due to the side effects of this medication. Seventy years old male patient that use ACE inhibitor for hypertension accepted to the clinic with the complaint of syncope. A bout of coughing has developed during electroencephalography recording and 10 seconds in duration of subcortical like epileptiform discharges were viewed. The ACE inhibitor the patient was receiving was replaced with calcium channel blocker and no complaint was observed during the follow up period. [Cukurova Med J 2015; 40(3.000): 619-622]